2021
DOI: 10.3389/pore.2021.629829
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside Protects HK-2 Cells Against High Glucose-Induced Apoptosis and Inflammation via the miR-499a-5p/NRIP1 Pathway

Abstract: Hyperoside, a flavonol glycoside, is derived from plants of the genera Hypericum and Crataegus. Recent studies have indicated the anti-apoptotic and anti-inflammatory roles of hyperoside. The present study was designed to measure the effects of hyperoside on high glucose (HG)-treated HK-2 cells. HK-2 is a human papillomavirus 16 transformed cell line and can be used as a model for normal tubular cell. Cell apoptosis was examined by TUNEL assays and flow cytometry analysis. Inflammatory response was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…miR-499a-5p has also been illustrated to play roles in the biological processes of various cells, such as the proliferation, differentiation, and metastasis of tumor cells [20,21,28,29]. Additionally, miR-499a-5p was also revealed to regulate the resistance of pancreatic cancer cells to chemotherapy and mediate the protective effect of hyperoside on high glucose-induced apoptosis of tubular cells [19,30]. In the present study, miR-499a-5p was observed to reverse the protective effect of LINC01018 on high glucose-induced pancreatic β cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-499a-5p has also been illustrated to play roles in the biological processes of various cells, such as the proliferation, differentiation, and metastasis of tumor cells [20,21,28,29]. Additionally, miR-499a-5p was also revealed to regulate the resistance of pancreatic cancer cells to chemotherapy and mediate the protective effect of hyperoside on high glucose-induced apoptosis of tubular cells [19,30]. In the present study, miR-499a-5p was observed to reverse the protective effect of LINC01018 on high glucose-induced pancreatic β cell.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between LINC01018 and miR-499a-5p was also predicted by the online software with several binding sites. Moreover, miR-499a-5p was reported to mediate the protective effect of hyperoside on high glucose-induced human tubule epithelial cell apoptosis 19 . miR-499a-5p could also regulate cell differentiation of mesenchymal stem cells and osteosarcoma cells 20 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hyp treatment (8, 65, and 500 mg/kg) for 38 weeks induced no abnormal reactions in symptoms, blood tests, and histological examination in Beagle dogs, and mild toxicity of the kidney and liver was negligible and reversible [ 98 ]. Other teams found that Hyp can contribute to the alleviation of renal cellular aging and injury in NRK-52E cells and rats exposed to D-galactose [ 99 ] as well as the protection of HK-2 (human renal proximal tubule cells) from high-glucose-induced apoptosis and inflammation [ 100 ].…”
Section: Safety Of Hyperosidementioning
confidence: 99%
“…In macrophages, NRIP1 can promote the activation of NF-κB and upregulate the expression of genes involved in the inflammatory response [ 4 ]. In high glucose treated HK-2 cells, Hyperoside downregulated the protein expression of NRIP1 dose-dependently, and reduced apoptosis and inflammatory response [ 5 ]. Another study showed that overexpression of NRIP1 induced proinflammatory cytokine release in cardiomyocytes, which could be reversed by p65 NF-κB inactivation.…”
Section: Introductionmentioning
confidence: 99%